Strategi Komunikasi Pemasaran Mave Magazine dalam Mempertahankan Eksistensi sebagai Majalah Lifestyle di Bali - Witono, Trisnawati; Pascarani, Ni Nyoman Dewi; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT   The mass media has became a medium that is needed by the society to search the latest information that is happening around them. As well as magazine, the evolution of mass media has became a challenge for Mave Magazine to survive as a lifestyle magazine. The main purpose on this research find out that Mave Magazine's marketing communication strategy in maintaining existence as a lifestyle magazine in Bali. The type of research using is a descriptive qualitative approach with a post-positivism paradigm. Data collection techniques are interviews and observations. Based on the results of interviews and observations, it found that Mave Magazine is maintaining its existence as a Bali lifestyle magazine by applying the promotional mix elements to the target market and also following the trends of media evolution so that Mave Magazine was always known to the public .  Keywords: Marketing Communication Strategic, Promotion Mix, Lifestyle Magazine.